The Mediating Role of Lifestyle in the Relationship Between Product Image and Local Food Purchase Decisions Among Generation Z in Ternate City (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of product image on local food purchasing decisions among Generation Z in Ternate City, with lifestyle as a mediating variable. The study used a quantitative approach with a survey design. The study population was Generation Z in Ternate City who had consumed local food. A sample of 150 respondents was determined using a purposive sampling technique with the criteria of respondents being Generation Z and having experience purchasing or consuming local food. Data were collected through questionnaires using a Likert scale. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) which included testing the measurement model (outer model), the structural model (inner model), and testing direct and indirect effects through mediation analysis using the Variance Accounted For (VAF) value. The results showed that product image had a positive and significant effect on purchasing decisions and lifestyle. Lifestyle also had a positive and significant effect on purchasing decisions. In addition, lifestyle was proven to partially mediate the relationship between product image and purchasing decisions with a VAF value of 43.97%. These findings indicate that local food purchasing decisions among Generation Z are influenced by a strong product image and supported by a lifestyle that is developing in the digital era.